Yaws' transport properties of chemicals and hydrocarbons - Yaws, Carl L. (Knovel, 2010)
Chemical and process engineers, chemists, chemical engineering students, and anyone involved in process design, plant operations, R & D, industrial health and safety, and many other fields where finding properties data is important will appreciate the unparalleled access to the invaluable data found in Transport properties of chemicals and hydrocarbons.
Title from eBook information screen.
Keywords: Organic compounds -- Transport properties -- Handbooks, manuals, etc.; Inorganic compounds -- Transport properties -- Handbooks, manuals, etc.; elektronické knihy; electronic books